Flexible h-BN foam sheets for multifunctional electronic packaging materials with ultrahigh thermostability. Issue 20 (14th May 2018) - Kim, Deul; Kirakosyan, Artavazd; Lee, Jae Woong; Jeong, Jong-Ryul; Choi, Jihoon
Abstract : Flexible and robust h-BN foam sheets with a three-dimensional network structure exhibit a much enhanced thermal conductivity as well as thermo-stability at high temperature. Abstract : Recently developed electronic packaging materials based on low dimensional materials such as carbon nanotubes, graphene, and hexagonal boron nitride (h-BN) exhibit advantageous electrical, thermal, and mechanical properties for protecting electronic devices as well as dissipating heat flux from highly integrated circuits or high power electronic devices. Their thermal transport is mainly achieved by precise control of the nanostructure for nano-fillers to form the thermally conductive pathway. However, due to the viscoelastic behaviors of host polymeric materials, their phase or structural stability is significantly reduced by enhanced molecular motion at high temperature, resulting in poor thermal transport and mechanical strength. Here, we introduce flexible and robust h-BN foam sheets with a three-dimensional network structure, which exhibit much enhanced thermostability at high temperature. Furthermore, the additional infiltration of Fe3 O4 nanoparticles into those structures results in relatively high electromagnetic absorbing performance. The combination of thermostability and mechanical strength based on the h-BN foam sheets provides novel opportunities for multifunctional thermally conductive materials in coatings and films without severely compromising auxiliary characteristics such as mechanical strength and thermal stability.